2019
DOI: 10.1093/mnras/stz2525
|View full text |Cite
|
Sign up to set email alerts
|

The morphological classification of distant radio galaxies explored with three-dimensional simulations

Abstract: We explore the observational implications of a large systematic study of high-resolution three dimensional simulations of radio galaxies driven by supersonic jets. For this fiducial study, we employ non-relativistic hydrodynamic adiabatic flows from nozzles into a constant pressurematched environment. Synchrotron emissivity is approximated via the thermal pressure of injected material. We find that the morphological classification of a simulated radio galaxy depends significantly on several factors with increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The size and time coverage of our data set provides a unique opportunity to examine the stability of the innermost regions of AGN jets over time. Although smoking gun evidence of AGN jet precession has been seen on kpc-scales (e.g., Smith & Donohoe 2019;Falceta-Gonçalves et al 2010;Gower et al 1982), there have been few large systematic pc-scale studies to date. In Lister et al (2013) we identified several individual cases of AGN that may be undergoing periodic changes in their inner jet position angle (PA).…”
Section: Introductionmentioning
confidence: 99%
“…The size and time coverage of our data set provides a unique opportunity to examine the stability of the innermost regions of AGN jets over time. Although smoking gun evidence of AGN jet precession has been seen on kpc-scales (e.g., Smith & Donohoe 2019;Falceta-Gonçalves et al 2010;Gower et al 1982), there have been few large systematic pc-scale studies to date. In Lister et al (2013) we identified several individual cases of AGN that may be undergoing periodic changes in their inner jet position angle (PA).…”
Section: Introductionmentioning
confidence: 99%
“…In real-world radio sources, hydrodynamic processes in lobes can push jets away from their ballistic paths, and may also disrupt them. Still, hydrodynamic models have also shown the development of characteristic precession signatures (e.g., Cox et al 1991;Donohoe & Smith 2016;Smith & Donohoe 2019), whilst such signatures are absent in simulations of non-precessing jets (e.g., English, Hardcastle & Krause 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The simulations analysed here have been introduced in Paper 1 (Donohoe & Smith 2016) for their physical attributes and in Paper 2 (Smith & Donohoe 2019). for their radio morphology and classification.…”
Section: Simulation and Display Parametersmentioning
confidence: 99%
“…We aim to account for the Mach number, pre-E-mail: m.d.smith@kent.ac.uk † E-mail: jd440@kent.ac.uk, cession and orientation in order to provide a rich bank of simulated images. The physical properties and radio morphologies have already been published for this set of three-dimensional simulations in Paper 1 (Donohoe & Smith 2016) and Paper 2 (Smith & Donohoe 2019). We thereby wish to probe the implications for the intracluster medium.…”
Section: Introductionmentioning
confidence: 99%